2020
DOI: 10.1021/acs.oprd.0c00247
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Green and Sustainable Manufacturing Process for Gefapixant Citrate (MK-7264). Part 5: Completion of the API Free Base via a Direct Chlorosulfonylation Process

Abstract: A scalable two-pot sulfonamidation through the process has been developed for the synthesis of gefapixant citrate, a P2X3 receptor antagonist that is under investigation for the treatment of refractory and unexplained chronic cough. Direct conversion of the diaryl ether precursor to a sulfonyl chloride intermediate using chlorosulfonic acid, followed by treatment with aqueous ammonia hydroxide, provided the desired sulfonamide in high yield. A pH-swing crystallization allowed for the formation of a transient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Unfortunately, although this process appeared quite efficient (95% yield with a process mass intensity (PMI) of 20), it suffered from major deficiencies as the slurry-to-slurry conversion: (1) often resulted in contamination of the citrate salt with significant amounts of the unreacted free base (up to 10 wt % in some batches); (2) did not offer the levels of form control and impurity rejection that would be obtained from a solution crystallization; and (3) offered no opportunity of a pure filtration step prior to the crystallization, to remove any extraneous insoluble matter which could arise from the penultimate step or from the equipment train. As a result of the inability to reject impurities in the API-forming step, the first-generation process relied on repeated recrystallizations of the free base to reject major chemical impurities, which contributed to the particularly high PMI for the preceding sulfonamidation step . These multiple issues render the first-generation citrate salt formation process unsuitable for commercial API production.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although this process appeared quite efficient (95% yield with a process mass intensity (PMI) of 20), it suffered from major deficiencies as the slurry-to-slurry conversion: (1) often resulted in contamination of the citrate salt with significant amounts of the unreacted free base (up to 10 wt % in some batches); (2) did not offer the levels of form control and impurity rejection that would be obtained from a solution crystallization; and (3) offered no opportunity of a pure filtration step prior to the crystallization, to remove any extraneous insoluble matter which could arise from the penultimate step or from the equipment train. As a result of the inability to reject impurities in the API-forming step, the first-generation process relied on repeated recrystallizations of the free base to reject major chemical impurities, which contributed to the particularly high PMI for the preceding sulfonamidation step . These multiple issues render the first-generation citrate salt formation process unsuitable for commercial API production.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge was addressed using a combination of one factor at a time (OFAT) experiments and impurity spiking experiments. As previously mentioned, process development for synthetic chemistry steps were occurring in parallel, so close collaboration with the free base step team was required for efficient evaluation and experimentation . For several key impurities, authentic samples were spiked to generate even higher levels than what was specified for the free base to investigate the purging capabilities of the co-feed process.…”
Section: Development Of the Co-feed Processmentioning
confidence: 99%
“…As previously mentioned, process development for synthetic chemistry steps were occurring in parallel, so close collaboration with the free base step team was required for efficient evaluation and experimentation. 11 For several key impurities, authentic samples were spiked to generate even higher levels than what was specified for the free base to investigate the purging capabilities of the co-feed process. This lab development demonstrated that the new cofeed process could achieve equivalent or better API purity compared to the batch process, as shown in Table 1.…”
Section: ■ Project Backgroundmentioning
confidence: 99%
“…At 25 °C, the acetonitrile solvate was more stable than the anhydrous form at >15 vol % acetonitrile (vs water). 52 The compound is crystallized via the addition of citric acid to a basic solution of compound B to afford the neutral compound B in ∼80/20 v/v water/acetonitrile. To demonstrate the impact of the crystal form on impurity rejection, two crystallizations were performed with the same feed stream and ending at the same solvent composition.…”
Section: Industrial Case Study 2: Impurity Forming Solid Solution Wit...mentioning
confidence: 99%